Stand-up Comedy sebagai Media Kritik Sosial (Analisis Wacana Digital pada Konten Program Adu Cuanda x TAYTB Women Warriors di Kanal Youtube OCBC) - Anwar, Naira Rafida; Zamzamy, Ahmad (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study Research This study analyzes the social criticism discourse presented by female comedians in the Adu Cuanda x TAYTB Women Warriors program on OCBC YouTube, placing digital media as a space for women's advocacy and empowerment. Based on Judith Butler's theory of gender performativity and Rodney H. Jones et al.'s analysis of digital discourse, this study highlights aspects of text, context, interaction, and power relations and ideology. The results show that the comedians raise issues of gender, culture, family, economics, politics, morals, and religion, including stereotypes, objectification, subordination, double burdens, socio-economic inequality, and religious and mental health stigma. These findings confirm that stand-up comedy functions as a medium for social criticism and empowerment, while YouTube serves as an inclusive digital space for the struggle for gender equality.